Pengaruh Modifikasi Lauk Nabati pada Makan Siang Terhadap Daya Terima Pasien Non Diet di RSUD Tamiang Layang: The Effect of Modification of Vegetable Side in Lunch on the Acceptance of Non-Diet Patients at Tamiang Layang Hospital - Munifa Munifa; Pretty Natalia (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Non-diet patients at Tamiang Layang Hospital often don't finish eating vegetable side dishes, so it is necessary to make changes to vegetable side dishes, namely by modifying the menu or recipe regarding ingredients, sizes, seasonings, and how to process them. The modifications made aim to improve the appearance and taste of vegetable side dishes, namely tofu and tempeh which are expected to increase the acceptance of non-diet patients. This study aims to determine the effect of modification of vegetable side dish recipes at lunch on the acceptance of non-diet patients at Tamiang Layang Hospital.This research is a quasy experimental study with a One Group Pretest-Posttest Design. The study was conducted in 2 stages, namely panelists and non-diet patients who were hospitalized at Tamiang Layang Hospital, East Barito Regency. Respondents in this study were 30 non-diet patients with certain criteria. Data analysis used the Mc Nemar and Wilcoxon tests. Result: Making a modified recipe for vegetable side dishes, namely tempeh nuggets and tofu cakes. It was found that 30 patients (100%) liked tempeh nuggets and 28 tofu cakes (93.4%) while non-diet patients liked tempeh nuggets and 16% for tofu cakes. The results of the McNemar test showed that there was an effect of modification of vegetable side dishes at lunch on acceptance, seen from the level of preference of non-diet patients at Tamiang Layang Hospital with p <0.05 and the results of the Wilcoxon test, there was an effect of modification of vegetable side dishes at lunch on acceptance, seen from leftovers. non-diet patients at Tamiang Layang General Hospital with p <0.05. Conclusion: There is an effect of modifying vegetable side dish recipes at lunch on the acceptability of non-diet patients at Tamiang Layang Hospital.